Reminiscences of Past Days with Prof. Dr. Mohammad Ali Asgar, Fellow, BAS - Ali, M Shamsher (Journal of Bangladesh Academy of Sciences, 2021)
Abstract not available. Journal of Bangladesh Academy of Sciences, Vol. 44, No. 2, iv-vii, 2020